PENGARUH GAP BLADE TIP TURBINE TERHADAP TIPSHOE PADA PERFORMANCE TEST ENGINE CENTAUR 40 TIPE 4501 SINGLE SHAFT - Nasywa Callista Imtiyaz; Victoriano Jonathan Lendeng; Wahyu Ramdani (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the effect of turbine blade tip gap on the tipshoe during the performance test of the Centaur 40 type 4501 single-shaft gas turbine engine. The research was conducted through a literature review, observation of the assembly process, and analysis of performance test data obtained from PT. Nusantara Turbin. The procedures included reassembling the main components of the Centaur 40 gas turbine, preparing the test setup through instrument calibration, lubrication system inspection, cleaning of air and fuel lines, and installing the turbine on the skid test bed. The measured performance parameters consisted of pressure (P1, P2), temperature (T1–T4), and turbine output power (Ẇsiklus). The results indicate that the blade tip gap significantly affects turbine performance. A larger gap reduces performance due to increased T4, decreased effective mass flow, and higher fuel flow, resulting in lower output power. Conversely, a smaller gap leads to optimal performance because more gas energy is absorbed by the turbine, reducing T4, increasing mass flow, and lowering fuel consumption. The study concludes that maintaining an appropriate gap clearance is essential for achieving optimal performance of the Centaur 40 gas turbine. Furthermore, the maintenance, repair, and overhaul (MRO) procedures performed were consistent with manufacturer standards and successfully restored engine performance.